2009
DOI: 10.1094/pdis-93-5-0519
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Crop Rotation for Verticillium Wilt Management and Effect on Pythium Species in Conventional and Organic Strawberry Production

Abstract: The effects of broccoli and lettuce rotations on population densities of Verticillium dahliae and Pythium spp. in soil and on strawberry (Fragaria × ananassa) growth, yield, and Verticillium wilt were evaluated in conventional and organic production systems in California for 2 years. Under both management systems, strawberry was planted after two successive crops of broccoli or lettuce. The control treatment in the conventional field was strawberry planted in soils fumigated with methyl bromide + chloropicrin.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 31 publications
(35 reference statements)
1
13
0
Order By: Relevance
“…The conventional farming system produced strawberry plants with higher leaf area and dry weight compared with the organic plants (Table 5). These results are consistent with previous reports (Baruzzi et al, 2009;Njoroge and Kabir, 2009) of a higher yield and canopy growth in the case of conventional management compared to organic farming. The different performances of the two farming methods did not appear to be caused by soil borne diseases, since no plant symptoms were detected, but they may be related to the faster action of the conventional mineral fertilizer compared to the organic manure.…”
Section: Plant Growth and Fruit Productionsupporting
confidence: 93%
“…The conventional farming system produced strawberry plants with higher leaf area and dry weight compared with the organic plants (Table 5). These results are consistent with previous reports (Baruzzi et al, 2009;Njoroge and Kabir, 2009) of a higher yield and canopy growth in the case of conventional management compared to organic farming. The different performances of the two farming methods did not appear to be caused by soil borne diseases, since no plant symptoms were detected, but they may be related to the faster action of the conventional mineral fertilizer compared to the organic manure.…”
Section: Plant Growth and Fruit Productionsupporting
confidence: 93%
“…Consequently, cultural practices that promote the expression of antimicrobial qualities within the resident microbiome, such as the application of organic matter or organic compound amendments (Akhtar and Malik 2000; Oka et al 2007;Alsanius et al 2009;Giotis et al 2009;Oka 2010;Lopes et al 2011;Somasekhara et al 2013) or the use of cover crops and rotation (Viaene and Abawi 1998;Njoroge et al 2009) help minimize disease pressure on the crop. Depending on the type of organic amendment and compost, multiple studies have reported a major or moderate suppressive effect of compost or compost tea on diseases such as bacterial spot (Xanthomonas vesicatoria), early blight (Alternaria solani), bacterial canker (Clavibacter michiganensis), corky root rot (Pyrenochaeta lycopersici), gray mould (B. cinerea), F.…”
Section: Disease Controlmentioning
confidence: 99%
“…Disease suppression by compost was also influenced by optimum soil conditions and nutrient supply. Crop rotation with broccoli (Brassica oleracea) to reduce the microsclerotia population in the soil and the postharvest incorporation of broccoli residues constitute a tool to limit Verticillium wilt in strawberry and cauliflower (Xiao et al 1998;Subbarao et al 2007;Njoroge et al 2009). …”
Section: Disease Controlmentioning
confidence: 99%
“…Likewise, wilt severity was also reduced to a greater extent in fi elds rotated with broccoli, compared with the fi elds rotated with lettuce. The usefulness of employing broccoli rotation coupled with postharvest incorporation of broccoli residue was indicated by this investigation (Njoroge et al 2009 ) .…”
Section: Crop Rotationmentioning
confidence: 93%